The cooperative type cooperative integrated reading and composition (CIRC) model is being used to enhance reading comprehension skills. - Arief Hasjaya; Sulkipli M; Irfandi Idris; Andi Maryam; Rizky Ekawaty Ahmad (Universitas Negeri Padang, 2022)
The Use of a Cooperative Learning Model of the CIRC Type to Improve Reading Comprehension Skills The research goal is to define cooperative learning model processes in order to improve reading comprehension skills in SD Muhammadiyah 2 Sorong City. This study makes use of classroom action research (CAR). The process of observing actions entails preparing, doing, observing, and reflecting. There are two cycles involved in accomplishing an action. With a total of 30 pupils, the topics were 4th grade in SD Muhammadiyah 2 in Sorong City. employing observation, questionnaires, interviews, and tests as methods of data collection. The study's finding indicates that using a cooperative learning model like CIRC can improve students in SD Muhammadiyah 2 Sorong City's fourth grade reading comprehension skills.